Academic mentoring and how it can support personalised learning - Smith, Lorraine D. (2014)
This study investigated how academic mentoring in two secondary schools in England could support personalised learning. The focus was limited to academic mentoring of year 11 students by members of staff, which aimed to improve academic performance.